Thermoelectric properties of single walled carbon nanotube networks in polycarbonate matrix. Issue 8 (10th June 2013) - Piao, Mingxing; Kim, Gyutae; Kennedy, Gary P.; Roth, Siegmar; Dettlaff‐Weglikowska, Urszula
Abstract We report on single walled carbon nanotubes (SWCNTs) used as a filler material for polycarbonate (PC) composites in this paper. Thin flexible composite films were prepared by solvent casting with a viscous dispersion of SWCNTs in a polymer matrix. The interaction of SWCNTs with PC was studied by Raman spectroscopy. Our investigations focus on the electrical conductivity and thermopower of the carbon nanotube network formed within the matrix. In this paper, we demonstrate that the incorporation of carbon nanotubes in the polymer composite profoundly modifies the electrical properties of the polymer composite in proportion with the SWCNT concentration. Although, the electrical conductivity of the composite increases by 16 orders of magnitude upon adding 1 wt% of SWCNTs, the Seebeck coefficient, which characterizes the thermoelectric properties, appears to be dominated by the type of polymer matrix and decreased slightly throughout the tested filler loading. A reasonable Seebeck coefficient of 65 µV K−1 was determined for these SWCNT composite films and, thus, suggests that thermoelectric power generation would be a good application for them. We also demonstrated that both the electrical conductivity and the Seebeck coefficient of SWCNTs embedded in a polymer can be efficiently modified by means of chemical treatments. In this way, flexible composite films exhibiting positive and negative Seebeck coefficients were fabricated. Assembling these films into a sandwich structure with alternating p/n junctions should produce a higher potential difference when a temperature gradient is applied across a multilayer thermoelectric device.